'Well, it literally stops me from having a life when it's really bad': a nested qualitative interview study of patient views on the use of self-management treatments for the management of recurrent sinusitis (SNIFS trial). Issue 11 (3rd November 2017) - Leydon, Geraldine M; McDermott, Lisa; Thomas, Tammy; Halls, Amy; Holdstock-Brown, Ben; Petley, Stephen; Wiseman, Clare; Little, Paul
Abstract : Objective: To explore the experience and perceptions of illness, the decision to consult a general practitioner and the use of self-management approaches for chronic or recurrent sinusitis. Design: Qualitative semistructured interview study. Setting: UK primary care. Participants: 32 participants who had been participating in the 'SNIFS' (Steam inhalation and Nasal Irrigation For recurrent Sinusitis) trial in the South of England. Method: Thematic analysis of semistructured telephone interviews. Results: Participants often reported dramatic impact on both activities and their quality of life. Participants were aware of both antibiotic side effects and resistance, but if they had previously been prescribed antibiotics, many patients believed that they would be necessary for the future treatment of sinusitis. Participants used self-help treatments for short and limited periods of time only. In the context of the trial, steam inhalation used for recurrent sinusitis was described as acceptable but is seen as having limited effectiveness. Nasal irrigation was viewed as acceptable and beneficial by more patients. However, some participants reported that they would not use the treatment again due to the uncomfortable side effects they experienced, which outweighed any symptom relief, which may have resulted had they continued. Conclusions: Steam inhalation is acceptable but seen as having limited effectiveness. Nasal irrigation is generally acceptable and beneficial for symptoms, but detailed information on the correct procedure and potential benefits of persisting may increase acceptability and adherence in those patients who find it uncomfortable. Trial registration number: ISRCTN 88204146.